Highly distorted Cr3+-doped fluoroantimonate with high absorption efficiency for multifunctional near-infrared spectroscopy applications. (December 2022) - Zhang, X.; Chen, K.; Deng, T.; Yuan, J.; Zhou, R.; Yu, T.; Zhou, Y.; Song, E.
Abstract: The growing near-infrared (NIR) spectroscopic technology has significantly prompted extensive exploration of broadband NIR-emitting phosphors. Cr 3+ -doped fluorides have recently emerged as a new prototype NIR emitter, whereas they endure low external quantum efficiency (EQE) limited by low absorption efficiency (AE < 30%). Here, an extremely high AE ∼56.2% is firstly realized in a highly distorted fluoroantimonate NaSbF4 and newly developed in multifunctional NIR spectroscopy applications. Formation energy and distortion index calculation demonstrate that Cr 3+ occupies an inherently highly distorted [SbF6 E] octahedron in a low local symmetry monoclinic structure and achieves a large parity-forbidden transition ( 4 T2 → 4 A2 ) probability of Cr 3+ . Moreover, NaSbF4 :Cr 3+ exhibits excellent stability against UV radiation, thermal impact, and extended device operation. The NIR phosphor-converted lighting-emitting diode (pc-LED) produces a photoelectric conversion efficiency of 10.48% at 20 mA and realizes non-destructive precision inspections of circuit boards, veins imaging, and night vision. Further combination with white pc-LED produces a full-VIS-NIR spectrum device applied to plant growth lighting. These findings open a new matrix model with aberrant crystal structures for high AE and advance the multifunctional NIR pc-LED applications covering industrial detection, bio-imaging, and modern agriculture. Graphical abstract: An efficient and thermally stable Cr 3+ NIR emission with a high AE of 56.2% is realized in a highly distorted NaSbF4 and applied in the multifunctional applications covering industrial detection, bio-imaging, and modern agriculture. Image 1 Highlights: An efficient NaSbF4 :Cr 3+ NIR phosphor presents a high QE of 54.5% and AE of 56.2%. DFT results show that highly distorted Cr 3+ lattice gains large parity-forbidden transition probability. NaSbF4 :Cr 3+ realizes multi-applications covering industrial detection, bio-imaging, and modern agriculture.